Serum proteomics for biomarker discovery in nonalcoholic fatty liver disease - YILMAZ, YUSUF (ELSEVIER SCIENCE BV, 2012)
Proteomic platforms have gained increasing attention in the clinical spectrum of nonalcoholic fatty liver disease (NAFLD). This approach allows for the unbiased discovery of circulating biochemical markers, i.e., it is not limited to known molecules of presumed importance. This manuscript provides an overview of proteomic serum biomarker discovery in NAFLD. Hemoglobin is currently the most widely replicated proteomic circulating biomarker of NAFLD; it was identified as a biomarker of fatty liver in two distinct proteomic studies and subsequently validated using distinct analytical methods by independent research groups in large replication cohorts. Given the increasing availability of numerous serum samples and the refinement of the technological platforms available to scrutinize the blood proteome, large collaborative studies between academia and industry are warmly encouraged to identify novel, unbiased circulating biomarkers of NAFLD. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Nonalcoholic fatty liver disease; Proteomics; Serum; Biomarkers; Hemoglobin; MASS-SPECTROMETRY; METABOLIC SYNDROME; NONINVASIVE DIAGNOSIS; CLINICAL PROTEOMICS; STEATOHEPATITIS; CHALLENGES; PATHOPHYSIOLOGY; BIOINFORMATICS; EPIDEMIOLOGY; HEMOGLOBIN